Пистолеты и револьверы: все о старинных пистолетах и револьверах / А. Сала - Сала Адриано (АСТ, 2008)
Экземпляры: 25 (20210706) / Инвентарный номер: 66412 / Цена: 150.00 / Сис.шифр: 68.512.12 / Авт.знак: С16 / ББК: 68.512.12